Radiation induced modification of dielectric and structural properties of Cu/PMMA polymer composites - (:unkn) unknown (My University, 2010)
In this study, composite films consisting of an insulating polymethyl methacrylate (PMMA) polymer matrix and metal powder (Cu) additive were prepared by solution costing method. These films were irradiated with 140 MeV silver ions at the fluences of 1 × 1011 ions/cm2 and 1 × 1012 ions/cm2. The radiation induced changes in dielectric, structural and surface properties of PMMA/Cu composites were studied using impedance/gain phase-analyzer, X-ray diffraction (XRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). It was observed that the dielectric properties and ac electrical conductivity increased significantly with the concentration of dispersed metal powder (Cu) and also with the fluence. This reveals that ion beam irradiation creates free radicals, unsaturation etc. due to emission of hydrogen and/or other volatile gases, which makes the polymer more conductive. XRD analysis of the pristine and irradiated samples shows that the crystallinity improved upon irradiation at low fluence and deteriorated on further increase of the fluence, which could be attributed to cross linking of polymer chains at low fluence and degradation at higher fluence. High energy ion beam irradiation of semicrystalline polymer composite films changes its Tg behavior as observed from DSC analysis. This result is also corroborated with the results of XRD. The average surface roughness and topography of surfaces changed with the concentration of filler and also with the ion fluence as revealed from AFM/SEM analysis. © 2010 Elsevier B.V. All rights reserved.
Keywords: Measurement techniques; Polymers and organics; Radiation; Thermal properties